Raising the white flag : how surrender defined the American Civil War - Silkenat, David (Civil War America (Series), 2019)
"Built on extensive archival research, Raising the White Flag presents the first comprehensive examination of why surrender featured so prominently in the Civil War. Looking at the Civil War from the perspective of men who surrendered opens new vistas onto familiar topics, providing fresh insights into the plight of prisoners of war, guerrilla warfare, Southern Unionists, and African American soldiers, the culture of honor, the experience of combat, and the laws of war"--